THE USE OF DESERT ISLAND ACTIVITY TO IMPROVE STUDENTS’ VOCABULARY - Thessa Hermita Entoh; Mister G. Maru; Maikel B. G. Sanger (SoCul: International Journal of Research in Social Cultural Issues, 2022)
This study intends to investigate the effectiveness of desert island activity in improving students' vocabulary. In conducting this research, the authors used quantitative research through post-test only with the experimental group and the control group. This research was conducted at SMPN 2 Tondano. The subject of the research is the 8th grade students at SMPN 2 Tondano. The findings show that the use of the desert island activity is very effective in improving students' English vocabulary skills. It further supports that choosing the right game and educating greatly influences the output of each learner. Therefore, the importance of the desert island activity in the process of learning English vocabulary for students, especially for the conditions of students in Indonesia with various learning styles, one of which is the Minahasa Regency, which has inadequate network access, can make the desert island activity a good reference to be recommended to students.